Indonesian Legal System Readiness in Utilizing Natural Resources in the Form of Forest Products to Face the ASEAN Economic Community (AEC) (Law Research Review Quarterly, 2015)
The 1945 Constitution of the Republic of Indonesia as the state constitution mandates the earth, water and natural resources contained in it to be controlled by the state and used as much as possible for the prosperity of the people, this should be a guideline for the government in formulating policies regarding the use of natural resources . However, the Rosidi case was deemed to have injured community justice and restricted access to forest products. This is interesting if related to the readiness of the legal system in Indonesia in dealing with the ASEAN economic community.